Solid electrolytic capacitors, smoothing circuits and filter circuits
By adding aromatic compounds with specific energy levels and hydroxy groups to solid electrolytic capacitors, the peroxidation degradation of conductive polymers is suppressed, thereby preventing capacitance deterioration in low-temperature environments.
Patent Information
- Application Number
- JP2024170900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-06
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-03-06
AI Technical Summary
Solid electrolytic capacitors with solid electrolyte layers and electrolyte solutions experience significant capacitance deterioration in low-temperature environments due to peroxidation degradation of conductive polymers.
Incorporating aromatic compounds with a HOMO energy level of -9.35 eV or higher and having one or more hydroxy groups into the solid electrolyte layer, the electrolyte solution, or both, to suppress peroxidation deterioration of conductive polymers.
The use of aromatic compounds effectively prevents capacitance deterioration in solid electrolytic capacitors at low temperatures, ensuring long-term stability and performance.
Smart Images

Figure 0007666723000022 
Figure 0007666723000023 
Figure 0007666723000024
Abstract
Description
[Technical field]
[0001] The present invention relates to a hybrid-type solid electrolytic capacitor that uses a solid electrolyte and an electrolytic solution in combination, a manufacturing method thereof, and a smoothing circuit and a filter circuit that include this solid electrolytic capacitor. [Background technology]
[0002] Capacitors are used in various applications, and are particularly widely used in filter circuits. Examples of filter circuits include low-pass filters, high-pass filters, band-pass filters, and ripple filters, also known as smoothing circuits. A smoothing circuit is provided in a power converter, and a smoothing capacitor is incorporated in the smoothing circuit. The power converter converts the power of an AC power source into DC power using a converter circuit, and converts the DC power into desired AC power using an inverter circuit. The smoothing circuit is interposed between the converter circuit and the inverter circuit, and suppresses and smoothes the pulsation of the DC output from the converter circuit before inputting it to the inverter circuit.
[0003] Electrolytic capacitors are widely used as capacitors. Electrolytic capacitors use valve metals such as tantalum or aluminum, and have an anode made of a sintered body made of valve metal powder or an anode made of an elongated foil made of valve metal etched to increase the surface area, thereby achieving a small size and large capacity. In particular, solid electrolytic capacitors, in which a dielectric oxide film is covered with a solid electrolyte, are small, have a large capacity, and have low equivalent series resistance, and are easy to form into chips and suitable for surface mounting. These are essential for the miniaturization, high functionality, and low cost of electronic devices.
[0004] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has excellent adhesion to dielectric oxide films, have rapidly become popular as solid electrolytes.
[0005] The conductive polymer may be a conductive polymer that exhibits electrical conductivity by using an external dopant. The external dopant may be a low molecular weight anion or a polyanion such as an organic sulfonic acid, and is used during chemical oxidation polymerization or electrolytic oxidation polymerization to exhibit high electrical conductivity. The conductive polymer may be a self-doped conductive polymer. The self-doped conductive polymer has a molecule acting as a dopant in the monomer molecule, and is endowed with electrical conductivity and solubility in a solvent.
[0006] However, compared to liquid-type electrolytic capacitors, in which the capacitor element is impregnated with an electrolytic solution and no solid electrolyte layer is used, solid electrolytic capacitors are poor at repairing defects in the dielectric oxide film. Therefore, so-called hybrid-type solid electrolytic capacitors, in which a solid electrolyte layer is formed on a capacitor element in which an anode foil and a cathode foil are opposed to each other, and the gaps in the capacitor element are impregnated with an electrolytic solution, have attracted attention (see, for example, Patent Document 1).
[0007] Here, in a solid electrolytic capacitor using both a solid electrolyte layer and an electrolyte solution, the conductivity deteriorates due to the de-doping reaction of the dopant, and the ESR of the solid electrolytic capacitor increases. In addition, in a high-temperature environment such as an atmosphere of 105°C, the solid electrolyte layer is oxidized and deteriorated, and the ESR of the solid electrolytic capacitor increases.
[0008] Regarding the increase in ESR accompanying the undoping reaction, Patent Document 1 reports that the undoping reaction can be suppressed by making the molar ratio of the acid component and base component, which are solute components in the electrolyte, acid-excessive. This report presumes that the undoping reaction is suppressed because the dopant, which is an acid component, and the acid component in the electrolyte maintain an equilibrium state.
[0009] In order to cope with the problem that oxidation of the solid electrolyte layer is accelerated in a high temperature environment, Patent Document 1 discloses that an antioxidant such as an aromatic compound such as phenol, methylphenol, ethylphenol, pyrogallol, hydroquinone, pyrocatechol, tocophenol, butylhydroxyanisole, dibutylhydroxytoluene, benzoic acid, salicylic acid, resorcylic acid, and benzotriazole, an amine compound, a silane compound, a quinone compound, and a carboxylic acid compound is contained in the electrolyte. Patent Document 1 describes the presumption that the antioxidant is activated and the deterioration suppression ability is increased because the hydrogen bond formed between the acid component and the antioxidant stabilizes the electronic resonance structure of the aromatic compound. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 4536625 Summary of the Invention [Problem to be solved by the invention]
[0011] It has been confirmed that, in a high-temperature environment, the increase in ESR of a solid electrolytic capacitor using a solid electrolyte in combination with an electrolytic solution can be suppressed by adding the antioxidant of Patent Document 1 to the electrolytic solution, but in a low-temperature environment, the deterioration of the capacitance of a solid electrolytic capacitor using a solid electrolyte in combination with an electrolytic solution may not be suppressed.
[0012] Fig. 1 is a graph showing the capacitance change (ΔCap) for each charge-discharge cycle in a solid electrolytic capacitor using both a solid electrolyte layer and an electrolyte solution at various temperatures and atmospheres. In Fig. 1, the circle plot is the graph in an atmosphere of 150°C, the triangle plot is the graph in an atmosphere of 0°C, and the square plot is the graph in an atmosphere of -40°C.
[0013] A voltage of 25V was applied and a peak current of 27A was applied, with one cycle consisting of charging and discharging repeated every 10 seconds. As shown in Figure 1, in a temperature environment of 150°C, the deterioration of ΔCap of the solid electrolytic capacitor using both a solid electrolyte layer and an electrolyte solution was suppressed. However, as shown in Figure 1, in a temperature environment of 0°C or lower, the ΔCap of the solid electrolytic capacitor using both a solid electrolyte layer and an electrolyte solution was significantly deteriorated.
[0014] The present invention has been proposed to solve the above-mentioned problems, and has an object to suppress deterioration of the capacitance of a solid electrolytic capacitor having a solid electrolyte layer and an electrolytic solution in a low-temperature environment. [Means for solving the problem]
[0015] As a result of intensive research, the present inventors have found that, unlike degradation based on chemical reactions accelerated by thermal energy, such as dedoping and oxidative degradation, which occur in conductive polymers in high-temperature environments, peroxidative degradation due to electrochemical reactions occurs in conductive polymers in low-temperature environments. That is, due to the current transient response during charging, a voltage is divided and applied to the solid electrolyte layer and the electrolyte during charge storage. Then, in low-temperature environments, this applied partial voltage causes peroxidation of the conductive polymer, which deteriorates the capacitance of the solid electrolytic capacitor.
[0016] However, the present inventors have confirmed that the phenomenon of peroxidative degradation of a conductive polymer due to charging and discharging in a low-temperature environment occurs significantly in so-called hybrid-type solid electrolytic capacitors in which a solid electrolyte layer containing a conductive polymer is used in combination with an electrolytic solution.
[0017] The solid electrolytic capacitor of Reference Example 1 having only a solid electrolyte layer and the solid electrolytic capacitor of Reference Example 2 having a solid electrolyte layer and an electrolytic solution were placed in a temperature environment of -40°C, and a load of 25V DC was applied, and 3100 charge / discharge cycles were repeated. One cycle consists of a 10-second charge and a 10-second discharge. The change in capacitance was measured before and after the 3100 charge / discharge cycles.
[0018] The measurement results are shown in Table 1 below. (Table 1) TIFF0007666723000001.tif31161
[0019] As shown in Table 1, the solid electrolytic capacitor of Reference Example 1, which has only a solid electrolyte layer, does not exhibit a decrease in capacitance in a low-temperature environment, despite the presence of a conductive polymer. On the other hand, the solid electrolytic capacitor of Reference Example 2, which has a solid electrolyte layer and an electrolytic solution, exhibits a large decrease in capacitance due to peroxidation of the conductive polymer.
[0020] Based on this finding, the inventors further conducted intensive research and found that the peroxidative degradation of the conductive polymer can be effectively suppressed by adding an aromatic compound having a higher HOMO energy level than the conductive polymer. In this case, the difference in HOMO energy levels between the conductive polymer and the aromatic compound is large, and the aromatic compound with a high HOMO energy level has a small difference with the electrode potential. Therefore, the aromatic compound can easily donate electrons to the electrode and is easily oxidized instead of the conductive polymer.
[0021] In particular, when the HOMO energy level is −9.35 eV or higher, the difference between the HOMO energy levels of the conductive polymer and the aromatic compound is large, and the aromatic compound having a high HOMO energy level has a small difference with the electrode potential, thereby improving the improvement rate of the capacitance. Based on this finding, the present inventors have completed the present invention.
[0022] That is, in order to solve the above problems, the solid electrolytic capacitor of the present embodiment includes an anode body, a cathode body, a solid electrolyte layer containing a conductive polymer, and an electrolyte solution, and the solid electrolyte layer, the electrolyte solution, or both, contain an aromatic compound having a HOMO energy level of −9.35 eV or higher and one or more hydroxyl groups.
[0023] The aromatic compound may be contained in an amount of 3.2 μmol or more per 1 mF of foil capacity of the anode body.
[0024] The aromatic compound may have a HOMO energy level of −8.88 eV or higher.
[0025] The aromatic compound may have a LUMO energy level of -1.88 eV or less. When the LUMO energy level is -1.88 eV or less, the aromatic compound is not only more easily sacrificially oxidized on the anode side than the conductive polymer, but also more easily reduced on the cathode side after oxidation. When the HOMO energy level is -9.35 eV or more, the aromatic compound having one or more hydroxyl groups is more easily regenerated on the cathode side. This makes it difficult for the aromatic compound to be depleted, and the deterioration of the capacitance of the solid electrolytic capacitor is prevented for a long time.
[0026] In particular, when the aromatic compound has a HOMO energy level of −8.88 eV or higher and a LUMO energy level of −1.88 eV or lower, the improvement rate of the capacitance of the solid electrolytic capacitor is significantly improved.
[0027] The aromatic compound may have hydroxy groups at the 1- and 4-positions.
[0028] The aromatic compound may further include one or more substituents.
[0029] The substituent may be an electron donating substituent or an acetyl group.
[0030] The electron donating substituent may be an alkyl group, an alkylene group, a vinyl group, a phenyl group, an amino group, a hydroxy group, or an alkoxy group.
[0031] The electron donating substituent may be located only at the 2-position of the 1,4-hydroxybenzene.
[0032] The electrolytic solution may contain a polyol compound as a solvent.
[0033] The electrolyte may contain glycerin as the polyol compound.
[0034] The conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid, and the concentration per volume of the capacitor element is 9.0 μg / mm 3 More than one may be included.
[0035] In order to solve the above problems, a smoothing circuit including the solid electrolytic capacitor of the present embodiment and a filter circuit including the solid electrolytic capacitor of the present embodiment are also aspects of the present invention.
[0036] In order to solve the above-mentioned problems, a method for producing a solid electrolytic capacitor according to the present embodiment includes the steps of forming a solid electrolyte layer containing a conductive polymer between an anode body and a cathode body, and impregnating the solid electrolyte layer with an electrolytic solution after the solid electrolyte layer is formed, wherein the solid electrolyte layer, the electrolytic solution, or both, contain an aromatic compound having a HOMO energy level of −9.35 eV or higher and one or more hydroxyl groups. Effect of the Invention
[0037] According to the present invention, it is possible to suppress the deterioration of the capacitance of a solid electrolytic capacitor including a solid electrolyte layer and an electrolytic solution in a low-temperature environment. [Brief description of the drawings]
[0038] [Figure 1]1 is a graph showing the change in capacitance (ΔCap) for each charge-discharge cycle in a solid electrolytic capacitor using both a solid electrolyte layer and an electrolytic solution under various temperature and atmosphere conditions. [Diagram 2] 1 is an example of a smoothing circuit including a solid electrolytic capacitor. [Diagram 3] 1 is an example of a filter circuit including a solid electrolytic capacitor. [Figure 4] 1 shows cyclic voltammograms of the conductive polymer film measured in the electrolyte solutions of Example 1 and Comparative Example 1, with the horizontal axis representing potential and the vertical axis representing current density. [Diagram 5] 1 is a graph showing the relationship between the HOMO energy level and the improvement rate of the capacitance. [Figure 6] 1 is a graph showing the relationship between the HOMO energy level, the LUMO energy level, and the improvement rate of the capacitance. [Figure 7] 1 is a graph showing the relationship between the ratio of glycerin in a solvent and the capacitance improvement rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] Hereinafter, a solid electrolytic capacitor according to an embodiment of the present invention will be described, however, the present invention is not limited to the embodiment described below.
[0040] (Overall composition) A solid electrolytic capacitor is a passive element that stores and discharges electric charge through capacitance caused by the dielectric polarization of a dielectric oxide film, and is classified as a so-called hybrid type that uses both a solid electrolyte layer and an electrolytic solution. Hereinafter, hybrid type solid electrolytic capacitors will be referred to simply as solid electrolytic capacitors.
[0041] A solid electrolytic capacitor is formed by housing a capacitor element in a case and sealing the opening of the case with a sealing member. The capacitor element includes an anode foil, a cathode foil, a separator, and an electrolyte layer. A dielectric oxide film is formed on the surface of the anode foil. The anode foil and the cathode foil face each other via the separator and are wound or laminated. The electrolyte layer includes a solid electrolyte layer and an electrolytic solution.
[0042] The solid electrolyte layer contains a conductive polymer such as poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid. This solid electrolyte layer is interposed between the anode foil and the cathode foil and is in close contact with the dielectric oxide film. An electrolyte solution is filled in the void of the capacitor element. The electrolyte layer functions as a true cathode. A specific aromatic compound (hereinafter referred to as the specific aromatic compound) is added to the electrolyte layer, i.e., the electrolyte solution, the solid electrolyte layer, or both, which oxidizes in place of the conductive polymer and thereby suppresses the peroxidative degradation of the conductive polymer.
[0043] An example of a method for manufacturing this solid electrolytic capacitor is outlined below: In the first step, an anode foil and a cathode foil, each having a dielectric oxide film formed on its surface, are wound with a separator therebetween to form a capacitor element, and the capacitor element is then subjected to a repair chemical conversion.
[0044] Then, in the second step, a solid electrolyte layer is formed on the capacitor element. In the second step, the capacitor element is impregnated with a conductive polymer liquid in which conductive polymer particles or powder are dispersed or dissolved, and the solvent is volatilized by drying. Then, in the third step, the capacitor element is impregnated with an electrolyte. The specific aromatic compound is added to the conductive polymer liquid, the electrolyte, or both.
[0045] Then, in a fourth step, the open end of the case into which the capacitor element is inserted is sealed with a sealant, and aging is then performed to form a solid electrolytic capacitor.
[0046] (Specific aromatic compounds) An aromatic compound (hereinafter, referred to as a specific aromatic compound) that oxidizes instead of a conductive polymer is added to the solid electrolyte layer, the electrolyte solution, or both. When the specific aromatic compound is added to the solid electrolyte layer, the specific aromatic compound may be added to a conductive polymer solution and impregnated into the capacitor element. A conductive polymer solution containing the specific aromatic compound may also be attached between the anode body and the cathode body. The specific aromatic compound is an aromatic compound having a HOMO energy level of -9.35 eV or higher and having one or more hydroxyl groups.
[0047] The HOMO energy level is the Highest Occupied Molecular Orbital energy level, also known as the highest occupied molecular orbital energy level, and is the molecular orbital with the highest energy occupied by electrons. Here, oxidation reaction is the phenomenon in which electrons are lost from a molecule. When electrons are lost, they are lost from the HOMO, which has the highest energy, that is, the electrons in the most unstable occupied orbital. In other words, the higher the HOMO energy level, the easier it is for electrons to be lost and the easier it is for oxidation reactions to occur. Also, the higher the HOMO energy level, the smaller the difference with the electrode potential, making it easier to donate electrons to the electrode. Therefore, relatively speaking, the higher the HOMO energy level, the easier it is to oxidize.
[0048] In this regard, for example, poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid has a calculated HOMO energy level of about -9.6 eV. A specific aromatic compound with a HOMO energy level of -9.35 eV or higher has a large difference in HOMO energy level with the conductive polymer and a small difference in electrode potential. Therefore, the specific aromatic compound is more likely to donate electrons to the electrode and is more likely to be oxidized instead of the conductive polymer. An aromatic compound having one or more hydroxyl groups undergoes an oxidation reaction in which the hydrogen atom of the hydroxyl group is eliminated to form a carbonyl group.
[0049] Therefore, in a low temperature environment of -20°C to -40°C, the conductive polymer of the solid electrolyte layer would normally be peroxidized and deteriorated, but the specific aromatic compound oxidizes before the conductive polymer, i.e., sacrificially oxidizes, suppressing the peroxidation of the conductive polymer and suppressing the deterioration of the capacitance of the solid electrolytic capacitor. In particular, aromatic compounds having a HOMO energy level of -8.88 eV or more and one or more hydroxyl groups are preferable because they have a good effect of suppressing the deterioration of the capacitance. For example, the HOMO energy level of the specific aromatic compound is -8.39 eV or less.
[0050] The HOMO energy level of poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid was calculated using a 16-mer of poly(3,4-ethylenedioxythiophene), in which five molecules at both ends of the molecular chain were in the undoped state and the central six molecules were in the doped state, as the molecular model, using the semiempirical molecular orbital method (MO-G) as the calculation program and the PM6 method as the calculation method.
[0051] The aromatic compound having a HOMO energy level of −9.35 eV or more and having one or more hydroxyl groups may be selected from the group consisting of hydroxybenzene-based aromatic compounds, aromatic compounds having a substituent on dihydroxybenzene, and carboxylic acids.
[0052] Among these, aromatic compounds having a HOMO energy level of -9.35 eV or more and one or more hydroxyl groups are preferably aromatic compounds having hydroxyl groups at the 1st and 4th positions, which tend to have a higher HOMO energy level and a higher peroxidation suppression effect on the conductive polymer. More preferably, aromatic compounds having hydroxyl groups at the 1st and 4th positions and further having one or more electron-donating substituents or acetyl groups are used, which tend to have a higher HOMO energy level and a higher peroxidation suppression effect on the conductive polymer. For example, aromatic compounds having hydroxyl groups at the 1st and 3rd positions can suppress dedoping and oxidative deterioration promoted by thermal energy, but have a relatively lower peroxidation suppression effect on the conductive polymer compared to aromatic compounds having hydroxyl groups at the 1st and 4th positions.
[0053] Such specific aromatic compounds include, for example, 1,4-dihydroxybenzene of the hydroxybenzene series, represented by the following chemical structural formula (1). [ka]
[0054] Another example of the hydroxybenzene series is sesamol, represented by the following chemical structural formula (2). [ka]
[0055] Another example of the hydroxybenzene series is 1,2-dihydroxybenzene represented by the following chemical structural formula (3). [ka]
[0056] Another example of the hydroxybenzene series is 1,2,3-trihydroxybenzene, represented by the following chemical structural formula (4). [ka]
[0057] Further, the specific aromatic compound is an aromatic compound having hydroxy groups at the 1-position and the 4-position and having one or more electron-donating substituents, such as an aromatic compound represented by the following chemical structural formula (5). [ka] In the chemical structural formula (5), the electron-donating substituent R is an alkylene group, a vinyl group, a phenyl group, an amino group, a hydroxyl group, an alkoxy group, an acyl group such as an acetyl group, an alkynyl group, or an alkyl group having one or more carbon atoms. In addition to the 2-position, the compound may have an electron-donating substituent R at other positions such as the 3-position and the 5-position.
[0058] An example of an aromatic compound having hydroxy groups at the 1- and 4-positions and one or more electron-donating substituents is methoxyhydroquinone represented by the following chemical structural formula (6). [ka]
[0059] An example of an aromatic compound having hydroxy groups at the 1- and 4-positions and one or more electron-donating substituents is tert-butylhydroquinone represented by the following chemical structural formula (7). [ka]
[0060] An example of an aromatic compound having hydroxy groups at the 1- and 4-positions and one or more electron-donating substituents is methylhydroquinone represented by the following chemical structural formula (8). [ka]
[0061] An example of an aromatic compound having hydroxy groups at the 1- and 4-positions and one or more electron-donating substituents is phenylhydroquinone represented by the following chemical structural formula (9). [ka]
[0062] An example of an aromatic compound having hydroxy groups at the 1- and 4-positions and one or more electron-donating substituents is 1,2,4-trihydroxybenzene represented by the following chemical structural formula (10). [ka]
[0063] Furthermore, the specific aromatic compound is an aromatic compound having hydroxy groups at the 1-position and the 4-position and also having an acetyl group, such as acetylhydroquinone of the following chemical structural formula (11). [ka]
[0064] Furthermore, examples of the specific aromatic compounds include, for example, vanillic acid represented by the following chemical structural formula (12) from the carboxylic acid series. [ka]
[0065] Furthermore, the specific aromatic compound may be, for example, gallic acid represented by the following chemical structural formula (13) from the carboxylic acid series. [ka]
[0066] Furthermore, examples of the specific aromatic compounds include, for example, 3,5-dihydroxybenzoic acid of the following chemical structural formula (14), which is a carboxylic acid. [ka]
[0067] More preferably, among the specific aromatic compounds, the aromatic compounds have a LUMO energy level of -1.88 eV or less. The LUMO energy level is the Lowest Unoccupied Molecular Orbital energy level, also called the lowest unoccupied molecular orbital energy level, and is the molecular orbital with the lowest energy among the orbitals with no electrons. A reduction reaction is a phenomenon in which electrons are given to a molecule. The electrons are added to the LUMO. The lower the LUMO energy level, the smaller the difference with the electrode potential, and the easier it is for electrons to be given from the electrode. Therefore, relatively speaking, the lower the LUMO energy level, the easier it is to reduce.
[0068] A specific aromatic compound with a HOMO energy level of -9.35 eV or higher is in a state where the hydrogen atom of the hydroxyl group is eliminated and changed to a carbonyl group by receiving electrons from the electrode. If the specific aromatic compound that has been converted to a carbonyl group by eliminating the hydrogen atom of the hydroxyl group has a low LUMO energy level, it can easily receive electrons from the electrode and obtain the hydrogen atom that was eliminated from the electrolyte. In other words, the carbonyl group returns to a hydroxyl group, and the specific aromatic compound is regenerated.
[0069] The regenerated specific aromatic compound again has the function of sacrificial oxidation prior to the peroxidation of the conductive polymer, and contributes to the suppression of the peroxidation of the conductive polymer. In particular, it has been found that the specific aromatic compound with a LUMO energy level of -1.88 eV or less is difficult to be depleted by regeneration, and the sacrificial oxidation prior to the peroxidation of the conductive polymer continues in the solid electrolytic capacitor. Therefore, a specific aromatic compound with a LUMO energy level of -1.88 eV or less is preferable, and this specific aromatic compound prolongs the effect of suppressing the deterioration of the capacitance of the solid electrolytic capacitor. In addition, for example, the LUMO energy level of the specific aromatic compound is -2.31 eV or more.
[0070] Specific aromatic compounds having a LUMO energy level of −1.88 eV or less include, for example, 1,4-dihydroxybenzene, 1,2-dihydroxybenzene, 1,2,3-trihydroxybenzene, tert-butylhydroquinone, methylhydroquinone, phenylhydroquinone, 1,2,4-trihydroxybenzene, acetylhydroquinone, and gallic acid.
[0071] In particular, when the aromatic compound has a HOMO energy level of −8.88 eV or higher and a LUMO energy level of −1.88 eV or lower, the improvement rate of the capacitance of the solid electrolytic capacitor is significantly improved.
[0072] The specific aromatic compound may be added alone or in combination of two or more kinds, but the amount of the specific aromatic compound added is preferably 3.2 μmol or more per 1 mF of foil capacity of the anode foil. When the amount of the specific aromatic compound added is within this range, the deterioration of the capacitance of the solid electrolytic capacitor is particularly suppressed. In particular, when the amount of the specific aromatic compound added is 6.7 μmol or more per 1 mF of foil capacity of the anode foil, the deterioration of the capacitance of the solid electrolytic capacitor is significantly suppressed.
[0073] The foil capacitance of the anode foil is measured by cutting a test piece of a specified area from the anode foil, immersing it in a capacitance measurement solution in a glass measuring tank with a platinum plate as the counter electrode, and measuring it with a capacitance meter. For example, the specified area is 1 cm 2 The capacitance measurement liquid is an aqueous solution of ammonium adipate at 30°C, the capacitance meter is a potentiostat and a frequency response analyzer, an electrochemical impedance analyzer, or an LCR meter, etc., and the measurement conditions are a DC bias voltage of 1.5V and an AC amplitude of 1V.
[0074] Regarding the amount of the specific aromatic compound to be added, the fact that a preferred numerical range can be obtained by using the foil capacity of the anode foil as a reference is presumed, and the mechanism is not limited to this, but it is considered that this is because the amount of conductive polymer tends to increase as the foil capacity of the anode foil increases, and the amount of conductive polymer on the anode foil is positively correlated with the foil capacity of the anode foil.
[0075] (Solid electrolyte layer) The conductive polymer contained in the solid electrolyte layer is a conjugated polymer of the self-doped type doped with dopant molecules within the molecule, or the externally doped type doped with external dopant molecules. Conjugated polymers are obtained by chemically oxidizing or electrolytically oxidizing a monomer having a π-conjugated double bond or its derivative. A dopant is an acceptor that easily accepts electrons into a conjugated polymer, or a donor that easily gives electrons to the conjugated polymer. In the case of an acceptor, π electrons are extracted from the conjugated polymer to form negative charge carriers (positive holes), and in the case of a donor, electrons are supplied to form negative charge carriers, and the conductive polymer exhibits conductivity.
[0076] This conductive polymer would normally deteriorate due to overoxidation in a low-temperature environment of -20°C to -40°C, but the specific aromatic compound oxidizes before the conductive polymer does, suppressing overoxidation. This prevents the capacitance of the solid electrolytic capacitor from deteriorating. When the specific aromatic compound is added, the conductive polymer content is 9.0 μg / mm2 per volume of the capacitor element consisting of the anode foil, cathode foil, and electrolyte layer. 3 When the content of the conductive polymer is within this range, the proportion of the conductive polymer that is inhibited from peroxidative degradation increases, and deterioration in the capacitance of the solid electrolytic capacitor is further inhibited.
[0077] As the conjugated polymer, any known polymer can be used without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. can be mentioned. These conjugated polymers can be used alone, or two or more kinds can be combined, or they can be copolymers of two or more kinds of monomers.
[0078] The conjugated polymer may be any known polymer without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These conjugated polymers may be used alone, or in combination of two or more kinds, or may be a copolymer of two or more kinds of monomers.
[0079] Among the above conjugated polymers, preferred are conjugated polymers obtained by polymerizing thiophene or its derivatives, and preferred are conjugated polymers obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof. As the thiophene derivative, a compound selected from thiophenes having substituents at the 3rd and 4th positions is preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The number of carbon atoms of the alkyl group or alkoxy group is preferably 1 to 16.
[0080] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, i.e., poly(3,4-ethylenedioxythiophene) called PEDOT, is particularly preferred. Also, a monomer in which a substituent is added to 3,4-ethylenedioxythiophene may be used. For example, an alkylated ethylenedioxythiophene in which an alkyl group is added as a substituent may be used, such as methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), etc.
[0081] The dopant may be a known one provided as a substituent of the conjugated polymer, or may be added in small amounts chemically or electrochemically, and may be used without any particular limitation. The dopant may be used alone or in combination of two or more kinds. The dopant may be a polymer of a single monomer, or a copolymer of two or more kinds of monomers. The dopant may be a polymer or a monomer.
[0082] Examples of the dopant include inorganic acids such as polyanions, boric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalateborate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid.
[0083] Examples of the polyanion include substituted or unsubstituted polyalkylene, substituted or unsubstituted polyalkenylene, substituted or unsubstituted polyimide, substituted or unsubstituted polyamide, and substituted or unsubstituted polyester, and include polymers consisting of only structural units having an anionic group, and polymers consisting of structural units having an anionic group and structural units not having an anionic group.Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.
[0084] In addition to the conductive polymer, the solid electrolyte layer may contain various additives such as polyhydric alcohols. Examples of polyhydric alcohols include sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyglycerin, polyoxyethyleneglycerin, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, and combinations of two or more of these. Since polyhydric alcohols have a high boiling point, they can remain in the solid electrolyte layer even after the drying process, and the effects of reducing ESR and improving voltage resistance can be obtained.
[0085] The method for forming the solid electrolyte layer is not particularly limited, and for example, a conductive polymer liquid in which conductive polymer particles or powder are dispersed or dissolved may be impregnated into a capacitor element, and the conductive polymer may be attached to a dielectric oxide film to form a solid electrolyte layer. In order to promote impregnation into the capacitor element, a decompression treatment or a pressurization treatment may be performed as necessary. The impregnation process may be repeated multiple times. The dispersion medium or solvent of the conductive polymer liquid is evaporated and removed by drying as necessary. Heat drying or reduced pressure drying may be performed as necessary.
[0086] Alternatively, a conductive polymer liquid may be applied or discharged between the anode body and the cathode body to form a solid electrolyte layer. By applying the conductive polymer liquid between the anode body and the cathode body, the conductive polymer liquid is applied to the dielectric film of the anode body, the cathode body, the separator, or a combination of these. Before assembling the capacitor element, the conductive polymer liquid may be applied individually to the dielectric film of the anode body, the cathode body, the separator, or a combination of these.
[0087] The conductive polymer liquid can be obtained, for example, by adding a monomer, an acid or an alkali metal salt thereof that releases a dopant, and an oxidizing agent, stirring the mixture until chemical oxidative polymerization is completed, and then removing the oxidizing agent and residual monomers by a purification means such as ultrafiltration, cation exchange, and anion exchange.
[0088] (electrolyte) The electrolyte may be impregnated between the anode body and the cathode body. For example, the electrolyte is impregnated into a capacitor element having a solid electrolyte layer formed thereon. The electrolyte is a solution in which an anion component and a cation component are added to a solvent. The anion component and the cation component are typically salts of an organic acid, salts of an inorganic acid, or salts of a complex compound of an organic acid and an inorganic acid, and are added to the solvent by an ion dissociative salt that dissociates into an anion component and a cation component. An acid that becomes an anion component and a base that becomes a cation component may be added separately to the solvent. In addition, the electrolyte does not need to contain an anion component or a cation component, or both an anion component and a cation component in the solvent.
[0089] The solvent of the electrolyte may be a protic organic polar solvent or an aprotic organic polar solvent. Examples of the protic organic solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Examples of the monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of the polyhydric alcohols and oxyalcohol compounds include ethylene glycol, diethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, and alkylene oxide adducts of polyhydric alcohols such as polyethylene glycol and polyoxyethylene glycerin.
[0090] As the aprotic organic polar solvent, sulfones, amides, lactones, cyclic amides, nitriles, sulfoxides, etc. may be used. Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, 2,4-dimethyl sulfolane, etc. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, etc. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, isobutylene carbonate, etc. Examples of nitriles include acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. The sulfoxides include dimethyl sulfoxide.
[0091] Among these solvents, polyol compounds are preferred when a specific aromatic compound is added. Combining a specific aromatic compound with a polyol compound enhances the effect of suppressing the deterioration of the capacitance of a solid electrolytic capacitor. Examples of polyol compounds include alkylene glycols such as ethylene glycol and propylene glycol, polyalkylene glycols such as polyethylene glycol, and glycerins such as glycerin and polyglycerin. In particular, combining a specific aromatic compound with a glycerin further enhances the effect of suppressing the deterioration of the capacitance of a solid electrolytic capacitor.
[0092] Glycerin is contained in the solvent at, for example, 20 wt % or more. Preferably, glycerin is contained in the solvent at 60 wt % or more. When the content is 60 wt % or more, the effect of suppressing the deterioration of the capacitance is suppressed to the same extent as when glycerin is 100 wt %.
[0093] In addition, it is preferable to add the specific aromatic compound to the electrolyte solution out of the solid electrolyte and the electrolyte solution, because the specific aromatic compound added to the electrolyte solution suppresses the deterioration of the capacitance of the solid electrolytic capacitor compared to the case where the specific aromatic compound is added to the solid electrolyte.
[0094] Examples of anion components in the electrolyte include oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, and other carboxylic acids, phenols, and sulfonic acids, and various other organic acids. Examples of inorganic acid anion components in the electrolyte include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.
[0095] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium salts include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc., examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.
[0096] Further, other additives can be added to the electrolyte. The additives may include phosphoric acid, phosphoric acid esters, and other phosphoric acid compounds, boric acid, boric acid esters, and other boric acid complexes with sugar alcohols such as mannitol and sorbitol, colloidal silica, silicone oil, and the like. The additives may also include nitro compounds. The nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzene, p-nitrobenzyl alcohol, m-nitroacetophenone, o-nitroanisole, and the like. As other additives, it is preferable to add phosphoric acid compounds such as phosphoric acid esters for the purpose of improving chemical conversion properties, or to add nitro compounds such as p-nitrobenzoic acid for the purpose of gas absorption.
[0097] (electrode foil) The anode foil and cathode foil facing each other with the electrolyte sandwiched therebetween are long foil bodies made of valve metals, such as aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity of the anode foil is preferably 99.9% or more, and that of the cathode foil is preferably about 99% or more, but impurities such as silicon, iron, copper, magnesium, and zinc may be included.
[0098] The anode foil is a sintered body obtained by sintering a powder of a valve metal, an etched foil obtained by etching a foil obtained by stretching a valve metal, or a vapor deposition body obtained by vapor-depositing valve metal particles on the surface of the foil, and the surface is enlarged. The enlarged surface structure is formed by tunnel-shaped pits, spongy pits, or gaps between densely packed powder particles. The tunnel-shaped pits may be dug leaving the deep part of the anode foil, or may be formed so as to penetrate the anode foil. This enlarged surface structure is formed by electrolytic etching, chemical etching, sandblasting, or the like, or by vapor-depositing or sintering metal particles or the like on the foil. Examples of electrolytic etching include DC etching or AC etching, in which a DC or AC current is applied in an acidic aqueous solution containing halogen ions such as hydrochloric acid. In addition, in chemical etching, the metal foil is immersed in an acidic or alkaline solution.
[0099] The dielectric oxide film is typically an oxide film formed on the surface layer of the anode foil, and if the anode foil is made of aluminum, it is aluminum oxide formed by oxidizing the porous structure region. This dielectric oxide film is formed by chemical conversion treatment in which a voltage is applied in an aqueous solution of adipic acid, boric acid, phosphoric acid, or the like.
[0100] The cathode foil may be a plain foil without a surface-expanding structure, or may have a surface-expanding structure by deposition, sintering, or etching, in the same manner as the anode foil. An oxide film may be formed intentionally or naturally on the surface-expanding layer. A thin dielectric oxide film (about 1 to 10 Vfs) may be intentionally formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode foil with oxygen in the air. An inorganic conductive layer may also be formed on the cathode foil. Examples of the inorganic conductive layer include metal compounds such as titanium and titanium carbide, and carbon.
[0101] (Separator) Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination.
[0102] (circuit) Such solid electrolytic capacitors are suitable for various filter circuits, such as low-pass filters, high-pass filters, band-pass filters, and ripple filters also known as smoothing circuits.
[0103] 2 is a circuit diagram showing an example of a smoothing circuit including this solid electrolytic capacitor. This smoothing circuit 1 includes a diode 2, a solid electrolytic capacitor 3, and an inrush current limiting circuit 4. The diode 2 is connected in series to the circuit, passes the rectified input voltage Vin, and prevents reverse connection. The solid electrolytic capacitor 3 is disposed after the diode 2 and connected in parallel to the circuit, smoothing the rectified input voltage Vin.
[0104] The inrush current limiting circuit 4 is inserted in series between the diode 2 and the solid electrolytic capacitor 3. The inrush current limiting circuit 4 includes a resistor 41 and a switch 42 connected in parallel. The resistor 41 limits the peak value of the inrush current input to the solid electrolytic capacitor 3. The switch 42 opens when an inrush current occurs and closes after the solid electrolytic capacitor 3 is charged, thereby shorting the resistor 41 and suppressing power loss.
[0105] In this smoothing circuit 1, in a low-temperature environment, the inrush current can cause the conductive polymer of the solid electrolytic capacitor 3 to deteriorate due to overoxidation, resulting in a decrease in capacitance. Therefore, the solid electrolytic capacitor 3 is replaced with a solid electrolytic capacitor whose HOMO energy level is -9.35 eV or higher and whose solid electrolyte layer, electrolyte solution, or both contain an aromatic compound having one or more hydroxyl groups. This suppresses the overoxidation of the conductive polymer of the solid electrolytic capacitor 3 caused by the inrush current, and also suppresses the decrease in capacitance. Therefore, a smoothing circuit 1 can be realized in which the resistor 41 that limits the peak value of the inrush current is replaced with one having a smaller resistance value.
[0106] In this smoothing circuit 1, the power loss is reduced because the resistance value of the resistor 41 is reduced. Therefore, the switch 42 can be omitted, and a smoothing circuit 1 can be realized in which the switch 42 is omitted rather than simply being replaced with a resistor 41 having a smaller resistance value.
[0107] Fig. 3 is a circuit diagram showing an example of a filter circuit including this solid electrolytic capacitor. The filter circuit 5 shown in Fig. 3 includes a solid electrolytic capacitor 3 and an inrush current limiting circuit 4. The solid electrolytic capacitor 3 is connected in parallel to the circuit, and the inrush current limiting circuit 4 is connected in series to the circuit before the solid electrolytic capacitor 3. The inrush current limiting circuit 4 includes a resistor 41 and a switch 42 connected in parallel.
[0108] Even in this filter circuit 5, in a low-temperature environment, the inrush current can cause the conductive polymer of the solid electrolytic capacitor 3 to deteriorate due to overoxidation, resulting in a decrease in capacitance. Therefore, the solid electrolytic capacitor 3 is replaced with a solid electrolytic capacitor whose HOMO energy level is -9.35 eV or higher and whose solid electrolyte layer, electrolyte solution, or both contain an aromatic compound having one or more hydroxyl groups. This makes it possible to realize a filter circuit 5 in which the resistor 41 that limits the peak value of the inrush current is replaced with one having a smaller resistance value.
[0109] In this filter circuit 5, the power loss is reduced because the resistance value of the resistor 41 is reduced. Therefore, it is possible to omit the switch 42, and a filter circuit 5 can be realized in which not only the resistor 41 is replaced with one having a smaller resistance value, but also the switch 42 is omitted. EXAMPLES
[0110] The solid electrolytic capacitor of the present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0111] (Electrolyte solution of Example 1) The electrolyte of Example 1 was prepared. For the electrolyte of Example 1, 0.16 mol of ammonium azelaate was added as a solute per 1 kg of electrolyte to an ethylene glycol solvent. Furthermore, 0.025 mol / kg of methoxyhydroquinone was added as a specific aromatic compound to the electrolyte of Example 1. Methoxyhydroquinone is an aromatic compound having hydroxyl groups at the 1st and 4th positions and a methoxy group, which is an electron-donating substituent, at the 2nd position. (Electrolyte solution of Comparative Example 1) An electrolyte solution of Comparative Example 1 was prepared corresponding to that of Example 1. The electrolyte solution of Comparative Example 1 has the same composition and composition ratio as that of Example 1, except that methoxyhydroquinone is not added.
[0112] (Peroxidation potential measurement test) Cyclic voltammograms showing the relationship between current and potential in a temperature environment of -40°C were analyzed for Example 1 and Comparative Example 1. The working electrode had a diameter of 3.0 mm and a surface area of 0.07 cm 2 The glassy carbon rod electrode was coated with a conductive polymer in advance. The conductive polymer was PEDOT / PSS, which is PEDOT doped with polystyrene sulfonic acid called PSS. This conductive polymer was coated on the glassy carbon rod electrode by solution casting. That is, a dispersion liquid in which PEDOT / PSS was dispersed was applied to the glassy carbon rod electrode, and then it was dried to volatilize the solvent of the dispersion liquid. 10 μL of the dispersion liquid was applied to the glassy carbon rod electrode and dried at 110 °C for 30 minutes.
[0113] A platinum electrode was used as the counter electrode, and an Ag / AgCl reference electrode was used as the reference electrode. The measurement solution used was a mixed solution of ethylene glycol as the solvent and ammonium azelaic acid as the supporting electrolyte (solute). 0.16 mol of ammonium azelaic acid was dissolved in 1 kg of the electrolyte. Then, potential scanning was started from the immersion potential to the positive side in a room temperature environment, and potential scanning was repeated between 1.5 V, which is more than 1.2 V, and -0.4 V.
[0114] FIG. 4(a) shows the result of a cyclic voltammogram of the conductive polymer film measured in the electrolyte of Example 1, and (b) shows the result of a cyclic voltammogram of the conductive polymer film measured in the electrolyte of Comparative Example 1, where the horizontal axis represents potential and the vertical axis represents current density.
[0115] As shown in FIG. 4(b), when the potential is scanned up to 1.5 V, it can be confirmed that the oxidation current and reduction current of the conductive polymer film are drastically reduced. During the charge-discharge test, the voltage is divided into the conductive polymer film and the electrolyte while the charge is stored due to the current transient response during charge-discharge. Therefore, in Comparative Example 1, in a temperature environment of -40°C, the voltage is divided and applied to the solid electrolyte layer during charge-discharge, and the partial pressure of 1.5 V causes the conductive polymer to deteriorate due to overoxidation associated with the electrochemical reaction.
[0116] 4(a), it can be confirmed that the change in the oxidation current and reduction current of the conductive polymer film is small in the electrolyte of Example 1, even when the potential is scanned up to 1.5 V. That is, the results of Comparative Example 1 and Example 1 confirm that in a low-temperature environment such as −40° C., the conductive polymer is peroxidized and deteriorated by an electrochemical reaction, but that the peroxidized deterioration of the conductive polymer due to the electrochemical reaction can be suppressed by adding the specific aromatic compound.
[0117] (Capacitor of Example 1) The solid electrolytic capacitor of Example 1 was produced using the electrolytic solution of Example 1. The anode foil was an aluminum foil, the surface of which was enlarged by etching, and a dielectric oxide film was formed by chemical conversion. In the chemical conversion treatment for the anode foil, a voltage was applied in an adipic acid aqueous solution. The cathode foil was an aluminum foil, the surface of which was enlarged by etching, and a dielectric oxide film was formed by chemical conversion, and a titanium compound was vapor-deposited. In the chemical conversion treatment for the cathode foil, a voltage was applied in an adipic acid aqueous solution.
[0118] A lead wire was connected to each of the anode and cathode foils, and the anode and cathode foils were wound facing each other with a manila separator interposed between them. The capacitor element was repaired by immersing it in an aqueous solution of ammonium dihydrogen phosphate for 10 minutes.
[0119] Next, a dispersion liquid of polyethylenedioxythiophene (PEDOT) doped with polystyrene sulfonic acid (PSS) was prepared, the capacitor element was immersed in it, the capacitor element was pulled out, and dried at 150°C for 30 minutes. The immersion and drying were repeated several times. As a result, a solid electrolyte layer was formed on the capacitor element. Then, the electrolyte solution of Example 1 was impregnated into the capacitor element on which the solid electrolyte layer was formed. At this time, the electrolyte solution was impregnated into the capacitor element so that the specific aromatic compound methoxyhydroquinone was 6.7 μmol / mF per 1 mF of the foil capacity of the anode foil.
[0120] The capacitor element was inserted into a cylindrical case with a bottom, a sealing body was attached to the open end, and the capacitor was sealed by crimping. A voltage was applied for 45 minutes in a temperature environment of 115°C, and the solid electrolytic capacitor of Comparative Example 1 was subjected to an aging treatment. The wound capacitor element with a diameter of 8.0 mm and a height of 10.0 mm thus produced was inserted into a cylindrical aluminum exterior case with a bottom, a sealing rubber was attached to the open end, and the capacitor was sealed by crimping. The rated withstand voltage of the solid electrolytic capacitor was 25 WV, and the rated capacity was 330 μF.
[0121] (Capacitors of Examples 2 to 12) Next, solid electrolytic capacitors of Examples 2 to 12 were produced. These solid electrolytic capacitors were all produced with the same configuration, manufacturing conditions, and manufacturing method as Example 1, except that the type of specific aromatic compound added to the electrolytic solution was different from that of Example 1. In addition, a solid electrolytic capacitor of Comparative Example 2 was produced. The solid electrolytic capacitor of Comparative Example 2 was all produced with the same configuration, manufacturing conditions, and manufacturing method as Example 1, except that the specific aromatic compound added to the electrolytic solution was not 3,5-dihydroxybenzoic acid.
[0122] In Example 2, tert-butylhydroquinone (t-BHQ) was added to the electrolyte as the specific aromatic compound. In Example 3, methylhydroquinone (MHQ) was added to the electrolyte as the specific aromatic compound. In Example 4, phenylhydroquinone (PhAHQ) was added to the electrolyte as the specific aromatic compound. In Example 5, 1,2,4-trihydroxybenzene was added to the electrolyte as the specific aromatic compound. In Example 6, sesamol was added to the electrolyte as the specific aromatic compound. In Example 7, 1,4-dihydroxybenzene was added to the electrolyte as the specific aromatic compound.
[0123] In Example 8, 1,2-dihydroxybenzene was added to the electrolyte as the specific aromatic compound. In Example 9, acetylhydroquinone was added to the electrolyte as the specific aromatic compound. In Example 10, 1,2,3-trihydroxybenzene was added to the electrolyte as the specific aromatic compound. In Example 11, vanillic acid was added to the electrolyte as the specific aromatic compound. In Example 12, gallic acid was added to the electrolyte as the specific aromatic compound.
[0124] (Charge / discharge test) The improvement rate of capacitance (ΔCap) was measured for the solid electrolytic capacitors of Examples 1 to 12 and Comparative Example 2. The capacitance was measured after placing each solid electrolytic capacitor in a temperature environment of -40°C, applying a load of 25V DC, and performing 540 cycles of charging for 10 seconds and discharging for 10 seconds. The improvement rate of capacitance was calculated using the following calculation formula 1.
[0125] (Formula 1) ΔCap = (Ca-Cb) ÷ Ca × 100 In the formula, Ca is the capacitance of the solid electrolytic capacitor of Comparative Example 1 to which the specific aromatic compound is not added, and Cb is the capacitance of the solid electrolytic capacitor of each Example and Comparative Example. An LCR meter (Agilent Technologies, 4284A) was used to measure the capacitance. In the measurement, the ambient temperature was 21°C, the AC current level was 1.0Vrms, and the measurement frequency was 120Hz.
[0126] The results of the improvement rate of the capacitance in Examples 1 to 12 and Comparative Example 2 are shown in Table 2 below. Table 2 further shows the position of the hydroxyl group, the type of the substituent, the HOMO energy level, and the LUMO energy level in the specific aromatic compound of each Example and the additive of Comparative Example 2. The HOMO energy level and the LUMO energy level were calculated by the PM6 method using a semi-empirical molecular orbital (MO-G) calculation program (SCIGRESS, manufactured by Fujitsu).
[0127] (Table 2) TIFF0007666723000016.tif146169
[0128] Based on Table 2, the relationship between the HOMO energy level and the improvement rate of capacitance is shown in the graph of Figure 5. As shown in Table 2 and Figure 5, the improvement rate of capacitance in Comparative Example 2 was only 3.9%, whereas the improvement rates of capacitance in Examples 1 to 12 exceeded at least 20%. Examples 1 to 12 are solid electrolytic capacitors containing aromatic compounds having a HOMO energy level of -9.35 eV or higher and one or more hydroxyl groups.
[0129] The capacitance improvement rate of Examples 1 to 9 exceeded at least 30%. Examples 1 to 9 are solid electrolytic capacitors containing aromatic compounds with a HOMO energy level of -8.88 eV or higher. Examples 1 to 9 are solid electrolytic capacitors containing dihydroxybenzene-based and hydroxybenzene-based aromatic compounds. Most of Examples 1 to 9 are solid electrolytic capacitors containing aromatic compounds having hydroxy groups at the 1,4 positions.
[0130] Based on Table 2, the relationship between the HOMO energy level, the LUMO energy level, and the improvement rate of the capacitance is shown in the graph of Figure 6. In Figure 6, the horizontal axis is the HOMO energy level, the vertical axis is the LUMO energy level, and the capacitance is shown beside the plot.
[0131] As shown in Table 2 and Figure 6, when the HOMO energy level is -8.88 eV or more, the capacitance improvement rate exceeds at least 30%. Furthermore, among the HOMO energy levels of -8.88 eV or more, Example 6, which has a LUMO energy level of more than -1.88 eV, has a capacitance improvement rate of 33%, while Examples 1 to 5 and Examples 7 to 9, which have a LUMO energy level of -1.88 eV or less, have a capacitance improvement rate of 38% or more. This result was obtained through a charge / discharge test of 540 cycles, and indicates that the specific aromatic compound was regenerated, thereby suppressing the deterioration of the capacitance even after this number of cycles.
[0132] It can also be seen that the capacitance improvement rates of Examples 1 to 4 and Example 9 in particular far exceed 40%. Examples 1 to 4 and Example 9 are aromatic compounds having hydroxy groups at the 1- and 4-positions and further having an electron-donating substituent or a substituent such as an acetyl group.
[0133] (Addition destination comparison test) The solid electrolytic capacitors of Examples 13 and 14 were further produced. In Examples 13 and 14, methylhydroquinone was used as the specific aromatic compound. In Examples 13 and 14, the specific aromatic compound was added to different destinations. That is, the objects to which the specific aromatic compound was added were different. In Example 13, the specific aromatic compound was added to the electrolytic solution as in Examples 1 to 9. On the other hand, in Example 14, the specific aromatic compound was added to the conductive polymer solution, and the capacitor element was immersed in the conductive polymer solution to form a solid electrolyte layer. That is, in the solid electrolytic capacitor of Example 14, the specific aromatic compound was contained in the solid electrolyte layer, and the specific aromatic compound was not added to the electrolytic solution.
[0134] The electrolyte was filled into the capacitor element so that the concentration of the specific aromatic compound was 14 μmol / mF per 1 mF of the foil capacity of the anode foil. Otherwise, the solid electrolytic capacitors of Examples 10 and 11 were produced with the same configuration, production conditions, and production method as Examples 1 to 9.
[0135] The improvement rate (ΔCap) of the capacitance was measured for the solid electrolytic capacitors of Examples 13 and 14. The capacitance was measured in the same manner as in Examples 1 to 9, including the fact that each solid electrolytic capacitor was placed in a temperature environment of -40°C.
[0136] The results of the capacitance improvement rates of Examples 13 and 14 are shown in Table 3 below. (Table 3) TIFF0007666723000017.tif31161
[0137] As shown in Table 3, in both Examples 13 and 14, the improvement rate of the capacitance is 45% or more. Therefore, whether the specific aromatic compound is added to the electrolyte or the solid electrolyte layer, the effect of suppressing the peroxidation degradation of the conductive polymer is exhibited, and it was confirmed that the deterioration of the capacitance of the solid electrolytic capacitor can be suppressed. Furthermore, Example 13 had a better improvement rate of the capacitance than Example 14. This confirmed that when the specific aromatic compound is added to the electrolyte, the peroxidation degradation of the conductive polymer in the solid electrolyte layer can be suppressed better.
[0138] (Addition amount test) Further, solid electrolytic capacitors of Examples 15 to 18, Reference Example 1, and Comparative Examples 3 and 4 were produced. In Examples 15 to 17 and Reference Example 1, the same acetylhydroquinone as in Example 9 was added to the electrolytic solution as the specific aromatic compound, but the amount added was different from that in Example 9. In addition, the solid electrolytic capacitors of Examples 15 to 17 and Reference Example 1 were produced by the same configuration, production conditions, and production method as in Example 9.
[0139] In Example 18, the same gallic acid as in Example 12 is added to the electrolyte as the specific aromatic compound, but the amount added is different from that in Example 12. Otherwise, the solid electrolytic capacitor of Example 18 was produced with the same configuration, production conditions, and production method as those in Example 12.
[0140] In Comparative Examples 3 and 4, the same 3,5-dihydroxybenzoic acid as in Comparative Example 2 was added to the electrolyte solution, but the amount added was different from that in Comparative Example 2. Otherwise, the solid electrolytic capacitors of Comparative Examples 3 and 4 were produced with the same configuration, production conditions, and production method as Comparative Example 2.
[0141] The improvement rate (ΔCap) of the capacitance was measured for the solid electrolytic capacitors of Examples 15 and 18, Reference Example 1, and Comparative Examples 3 and 4. The capacitance was measured in the same manner as in Examples 1 to 9, including the point that each solid electrolytic capacitor was placed in a temperature environment of -40°C.
[0142] The results of the capacitance improvement rates of Examples 9, 15 to 18, Reference Example 1, and Comparative Examples 2 to 4 are shown in Table 4 below together with the amounts of the specific aromatic compounds added. The amounts added in the table are the amounts added per 1 mF of the foil capacity of the anode foil (μmol / mF). (Table 4) TIFF0007666723000018.tif101161
[0143] As shown in Reference Example 1, Example 9, and Examples 15 to 18 in Table 4, it can be confirmed that the improvement rate of the capacitance of the solid electrolytic capacitor is improved by increasing the amount of the specific aromatic compound added. That is, as the amount of the specific aromatic compound added increases, the effect of suppressing the peroxidation degradation of the conductive polymer is further enhanced, and the effect of suppressing the deterioration of the capacitance of the solid electrolytic capacitor is improved. This tendency is also seen in Comparative Examples 2 to 4, but the improvement rate of the capacitance in Comparative Examples 2 to 4 is very small.
[0144] However, as shown in Reference Example 1, if the amount of the specific aromatic compound added is too small, the improvement rate of the capacitance is small, and it can be confirmed that the amount of the specific aromatic compound added is preferably 3.2 μmol or more per mF of foil capacity of the anode foil, as shown in Examples 15 and 18. Furthermore, as shown in Examples 9 and 17, if the amount of the specific aromatic compound added is 6.7 μmol or more per mF of foil capacity of the anode foil, the improvement rate of the capacitance is further increased.
[0145] (Electrolyte Solvent Volume Test) The solid electrolytic capacitors of Examples 19 to 21 were further prepared. The electrolyte filled in the solid electrolytic capacitors of Examples 19 to 21 contained 0.16 mol of azelaic acid triethylamine salt per 1 kg of electrolyte as a solute in the solvent. Furthermore, 0.025 mol / kg of methylhydroquinone was added to the electrolyte as a specific aromatic compound.
[0146] The electrolyte solutions filled in Examples 19 to 21 differ in the type of solvent. The electrolyte solution in Example 19 contains ethylene glycol, which is a polyol compound, as a solvent, the electrolyte solution in Example 20 contains glycerin, which is a polyol compound, as a solvent, and the electrolyte solution in Example 21 contains γ-butyrolactone as a solvent. Otherwise, the solid electrolytic capacitors in Examples 19 to 21 were produced with the same configuration, production conditions, and production method as Examples 1 to 9.
[0147] The improvement rate (ΔCap) of the capacitance was measured for the solid electrolytic capacitors of Examples 19 to 21. The capacitance was measured in the same manner as in Examples 1 to 9, including the fact that each solid electrolytic capacitor was placed in a temperature environment of -40°C.
[0148] The results of the capacitance improvement rate for Examples 19 to 21 are shown in Table 5 below, together with the type of solvent in the electrolyte. (Table 5) TIFF0007666723000019.tif41161
[0149] In Examples 19 and 20 in Table 5, the improvement rate of the capacitance of the solid electrolytic capacitor is improved compared to Example 21. That is, when a specific aromatic compound is added to the electrolyte layer, by further selecting a polyol compound as the solvent type of the electrolyte solution, the effect of suppressing the peroxidation degradation of the conductive polymer is further enhanced, and the effect of suppressing the deterioration of the capacitance of the solid electrolytic capacitor is improved. In addition, when glycerin is selected as the polyol compound, the effect of suppressing the peroxidation degradation of the conductive polymer and the effect of suppressing the deterioration of the capacitance are particularly enhanced.
[0150] (Conductive polymer test) Further, solid electrolytic capacitors of Examples 22 to 25 were produced. The solid electrolytic capacitors of Examples 22 to 25 were the same as the solid electrolytic capacitor of Example 3 in that the type of conductive polymer was polyethylenedioxythiophene (PEDOT) doped with polystyrene sulfonate (PSS), but the amount of conductive polymer was different.
[0151] The solid electrolytic capacitor of Example 25 has a different amount of the specific aromatic compound added compared to the solid electrolytic capacitor of Example 3. Otherwise, the solid electrolytic capacitors of Examples 22 to 25 were produced with the same configuration, production conditions, and production method as Example 3.
[0152] The improvement rate (ΔCap) of the capacitance was measured for the solid electrolytic capacitors of Examples 22 to 25. The capacitance was measured in the same manner as in Examples 1 to 9, including the fact that each solid electrolytic capacitor was placed in a temperature environment of -40°C.
[0153] The results of the improvement rate of the capacitance in Examples 19 to 21 are shown in Table 6 below, together with the amount of the conductive polymer. In the table, the amount of the conductive polymer is calculated based on the unit volume of 1 mm of the capacitor element consisting of the anode foil, the cathode foil, the separator, and the electrolyte layer. 3 It is expressed in hits. (Table 6) TIFF0007666723000020.tif69167
[0154] As shown in Table 6, the improvement rate of the capacitance of the solid electrolytic capacitor in Examples 3, 22 and 23 is higher than that in Examples 24 and 25. That is, when a specific aromatic compound is added to the electrolyte layer, the amount of the conductive polymer is further increased by 1 mm per unit volume of the capacitor element. 3 It was confirmed that by setting the amount to 9.0 μg or more per unit area, the effect of suppressing the peroxidative degradation of the conductive polymer was further improved, and the effect of suppressing the deterioration of the capacitance of the solid electrolytic capacitor was also improved.
[0155] In this embodiment, a cathode foil was used that was etched, then chemically converted, and then vapor-deposited with a titanium compound. However, it has been confirmed that the same effect as in this embodiment can be obtained by using a cathode foil that is not vapor-deposited with a metal compound.
[0156] Furthermore, solid electrolytic capacitors of Examples 26 to 30 were produced. The solid electrolytic capacitors of Examples 26 to 30 differ from Example 21 in the solvent ratio of glycerin and gamma-butyrolactone. Otherwise, the solid electrolytic capacitors of Examples 26 to 30 were produced with the same configuration, manufacturing conditions, and manufacturing method as Example 21. As shown in Table 7 below, the electrolytic capacitors of Examples 26 to 30 differ in the ratio of glycerin in the solvent in 10 wt% increments within the range from 20 wt% to 60 wt%.
[0157] Then, the improvement rate (ΔCap) of the capacitance was measured for the solid electrolytic capacitors of Examples 26 to 30. The capacitance was measured in the same manner as for Examples 1 to 9, including the point that each solid electrolytic capacitor was placed in a temperature environment of -40°C.
[0158] The results of the improvement rate of capacitance are shown in Table 7 below, together with those of Examples 21 and 20. The results of Table 7 below are shown in Figure 7. Figure 7 is a graph showing the relationship between the ratio of glycerin in the solvent and the improvement rate of capacitance.
[0159] (Table 7) TIFF0007666723000021.tif88157
[0160] 7, Example 26, in which the ratio of glycerin in the solvent is 20 wt%, has a higher improvement rate in capacitance than Example 21, in which no glycerin is added. When the ratio of glycerin is 60 wt% or more, as can be seen by comparing with Example 20, an improvement effect similar to that of 100 wt% glycerin is obtained.
Claims
1. an anode body and a cathode body; A solid electrolyte layer including a conductive polymer; An electrolyte; Equipped with the solid electrolyte layer, the electrolyte solution, or both, comprise an aromatic compound having a HOMO energy level of −9.35 eV or higher and one or more hydroxy groups; The aromatic compound has hydroxy groups at the 1- and 4-positions and further has one or more substituents; A solid electrolytic capacitor characterized by:
2. The aromatic compound has a HOMO energy level of −8.88 eV or higher; 2. The solid electrolytic capacitor according to claim 1,
3. The aromatic compound has a LUMO energy level of −1.88 eV or less; 2. The solid electrolytic capacitor according to claim 1,
4. the substituent is an electron donating substituent or an acetyl group; 2. The solid electrolytic capacitor according to claim 1,
5. the electron-donating substituent is an alkyl group, an alkylene group, a vinyl group, a phenyl group, an amino group, a hydroxyl group, or an alkoxy group; 5. The solid electrolytic capacitor according to claim 4,
6. the electron-donating substituent is located only at the 2-position of the 1,4-hydroxybenzene; 6. The solid electrolytic capacitor according to claim 5,
7. The electrolytic solution contains a polyol compound as a solvent; 2. The solid electrolytic capacitor according to claim 1,
8. The electrolyte solution contains glycerin as the polyol compound; 8. The solid electrolytic capacitor according to claim 7,
9. The conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid, and the concentration per volume of the capacitor element is 9.0 μg / mm 3 The above includes:
2. The solid electrolytic capacitor according to claim 1 .
10. The solid electrolytic capacitor according to claim 1 is provided. A smoothing circuit characterized by:
11. The solid electrolytic capacitor according to claim 1 is provided. A filter circuit comprising:
Citation Information
Patent Citations
Conductive porous body and its manufacturing method, and electrochemical device
JP2007095507A
Solid electrolyte, electrolytic capacitor, and manufacturing method thereof
JP2007103558A
Electrolyte for electrolytic capacitors and electrolytic capacitors using the same
JP4536625B2